Missing in action ; Foul! ; At home in Itbayat [videorecording] - Lazaro, Cheche (The Probe Team, 1993)
Deals with the case of Olongapo journalist Romy Legaspi who has been missing. Weena Lim, a badminton player taken out from Southeast Asian Games made charges of unfair treatment, nepotism and corruption against officials of the Philippine Badminton Association. Spanish priest Fr. Dennis Domingo has made his home in Itbayat, Batanes for 25 years now.